Differential effects of young and old hematopoietic stem cell niches on bone marrow-derived dendritic cells - Patrik Milić; Mojca Justin Kjuder; Katerina Jazbec Gradišar; Urban Švajger; Primož Rožman (Immunity & Ageing)
Abstract Background Aging is linked to various dysfunctions of the immune system, including the decline of its primary developmental source: the hematopoietic stem cell (HSC) niche. This decline leads to chronic inflammation, increased vulnerability to infections, cancer, autoimmune diseases, and reduced vaccine efficacy. As individuals age, the HSC niche undergoes significant changes, including greater adipocyte accumulation and alterations in the molecular microenvironment, which may influence the development and function of immune cells. Among these cells, the impact of the aging HSC niche on dendritic cell (DC) function is less understood. Heterochronic autologous HSC transplantation is a promising intervention to prevent age-related disorders, contributing to the extension of healthspan and longevity, however, several murine experiments failed to produce the expected results, which led us to presume that the problem lies within the old HSC niche. Therefore, we created in vitro models of young and old HSC niches and examined how these microenvironments affect the differentiation and maturation and functionality of BM-derived DCs (BMDCs). Results An analysis of the conditioned media from young and aged HSC niches revealed that the environment of aged niches exhibited an increased presence of adiponectin. This media was subsequently utilized in BMDC differentiation and maturation protocols, with their effects closely monitored. Our results indicate that the old HSC niche microenvironment promotes premature BMDC activation, characterized by elevated MHC class II expression and enhanced allostimulatory capacity of BMDCs at their immature stage. Additionally, LPS stimulation of BMDCs, used to induce DC maturation, significantly increased CD86 expression on BMDCs from the aged niche. However, these cells did not show superior allostimulatory capacity compared to their counterparts from the young niche environment. By analyzing the BMDC cytokine profile, we observed that when cultured in aged niche-conditioned media, the BMDCs secreted significantly higher levels of IL-6, indicating a heightened proinflammatory activation state. Conclusions Collectively, our findings suggest that aging-related changes within the HSC niche can considerably alter DC functionality by disrupting their normal development from BM precursors. These results emphasize the significance of this phenomenon and its implications for immunosenescence.